Virtual reality exposure therapy for armed forces veterans with Post-Traumatic Stress Disorder: a systematic review and focus group - Vianez, Ana Claúdia Gordo (2022)
This study aims to determine the guidelines for designing a Virtual Reality - War Scenario program for Armed Forces veterans diagnosed with Post-Traumatic Stress Disorder. This article encompasses two studies: Study 1, a systematic review of eleven articles indexed in the databases B-on, PubMed, Clinical trials and Cochrane Library; Study 2, a focus group of Portuguese armed forces veterans, discussed the outline of such a programme. A set of guidelines were identified as central and consensual, which should be included in the program. This type of program must have a realistic, multisensorial and interactive approach that allows veterans to re-adapt to their past, which is still so present. Virtual reality offers veterans with Post-Traumatic Stress Disorder unlimited opportunities, enhancing a personalized intervention. The results support the use of VRET as an efficacious treatment for combat-related PTSD, but suggest nevertheless, VRET, as a co-creation process, requires more controlled and in-depth research on their clinical applicability.